ASSESSING EFL STUDENTS’ WORD RECOGNITION AND READING ALOUD USING INFORMAL READING INVENTORIES - Syifa, Afifah Nurul; Hidayat, Hamdan; Novarita, Paulina (TELL - US JOURNAL, 2025)
Reading is one of the skills that plays a role in expanding vocabulary, mastering reading content, and sentence structure. Word recognition skills, reading accuracy, and reading rate are aspects that need to be improved. Therefore, teachers can find out the abilities of each individual student through various assessment media. This study aims to determine whether the Informal Reading Inventory (IRI) can assess students' word recognition and reading aloud abilities, as well as determine how many words students can say in one minute. The author used a qualitative method with a descriptive research design involving 32 eighth-grade students as participants. Data were obtained through interviews with English teachers, oral reading tests, and students' perceptions of the IRI implementation. The results showed that some students still had difficulty recognizing words, and many students made pronunciation errors on words they were less familiar with. The word recognition assessment results indicated that 17 students were still at the Frustration level. In terms of reading accuracy, all students had difficulty reading the word “Frightened.” Regarding reading comprehension ability, 15 students scored below 50%, while in terms of reading speed, students were at the second level. This study concluded that the use of IRI is effective as an assessment media to identify students' individual reading abilities. This study emphasizes the importance of training and providing varied learning media to improve students' word recognition and reading aloud abilities.